INOVASI DAN STRATEGI PEMASARAN PENDIDIKAN ISLAM DI TENGAH PERSAINGAN GLOBAL - Arisman Juanda (Hijri, 2025)
The era of globalization requires Islamic educational institutions to adapt to the increasingly fierce dynamics of global competition. Competition occurs not only between conventional educational institutions, but also with international institutions that offer technology-based educational services and global quality. This study aims to analyze the concepts, strategies, and innovations of Islamic education marketing in the context of modern global-oriented management. The research method used is a literature study with a descriptive-analytical approach. The results show that Islamic educational institutions need to integrate Islamic values with modern marketing strategies through religious branding, digital marketing, strengthening service quality, and curriculum innovation relevant to global needs. In conclusion, the success of Islamic education marketing in the global era is highly dependent on the ability of institutions to manage innovation and maintain competitive advantages based on spiritual values and professionalism.